Case Report: Prenatal Whole-Exome Sequencing to Identify a Novel Heterozygous Synonymous Variant in NIPBL in a Fetus With Cornelia de Lange Syndrome - Qiao, Fengchang; Zhang, Cuiping; Wang, Yan; Liu, Gang; Shao, Binbin; Hu, Ping; Xu, Zhengfeng (Frontiers in Genetics, 2021)
Cornelia de Lange syndrome (CdLS) is a genetically heterogeneous disorder characterized by a wide spectrum of abnormalities, including craniofacial dysmorphism, upper limb anomalies, pre- and postnatal growth restrictions, hirsutism and intellectual disability. Approximately 60% of cases are caused by NIPBL variants. Herein we report on a prenatal case presented with bilateral upper-extremity malformations and cardiac defects. Whole-exome sequencing (WES) was performed on the fetus–parental trio and a de novo heterozygous synonymous variant in NIPBL (chr5:37020979; NM_133433.4: c.5328G>A, p.(Gln1776=)) was identified. Reverse transcriptase–polymerase chain reaction (RT–PCR) was conducted to evaluate the potential splicing effect of this variant, which confirmed that the variant caused a deletion of exon 27 (103 bp) by disrupting the splice-donor site and changed the reading frame with the insertion of at least three stop codons. Our finding not only expands the mutation spectrum of NIPBL gene but also establishes the crucial role of WES in searching for underlying genetic variants. In addition, our research raises the important issue that synonymous mutations may be potential pathogenic variants and should not be neglected in clinical diagnoses.